Efficient induction and rapid identification of haploid grains in tetraploid wheat by editing genes TtMTL and pyramiding anthocyanin markers - Chang, Yanan; Tang, Huali; Wang, Surong; Li, Xi; Huang, Peipei; Zhang, Jiahui; Wang, Ke; Yan, Yueming; Ye, Xingguo (Frontiers in Plant Science, 2024)
Doubled haploid (DH) technology provides an effective way to generate homozygous genetic and breeding materials in a short period. We have produced three types of homozygous TtMTL gene edited mutants (mtl-a, mtl-b, and mtl-ab) by CRISPR/Cas9 in durum wheat. The PCR-restriction enzyme and sequencing confirmed that the editing efficiency was up to 53.5%. Seed setting rate of the three types of mutants ranged from 20% to 60%. Abnormal grain phenotypes of kernel abortion, embryo abortion, and both embryo and endosperm abortion were observed in progenies of the mutants. The average frequency of embryoless grains was 25.3%.Chromosome counting, guard cell length, and flow cytometry confirmed that the haploid induction rate was in a range of 3%-21% in the cross-and self-pollinated progenies of the mtl mutants (mtl-a and mtl-ab). Furthermore, we co-transformed two vectors pCRISPR/Cas9-MTL and pBD68-(ZmR+ZmC1) into durum wheat for pyramiding Ttmtl-edited mutations and embryo-specifically expressed anthocyanin markers, and developed a homozygous durum haploid inducer with purple embryo (DHIPE). Using the DHIPE as the male parent to be crossed with the wild-type Kronos, the grains with white embryos were identified to be haploid, while the grains with purple embryos were diploid. These findings will promote breeding for new varieties in tetraploid wheat.